1961
DOI: 10.1042/bj0780680
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulphate oxidation and cytochromes in Thiobacillus X. 2. Thiosulphate-oxidizing enzyme

Abstract: P. A. TRUDINGER 1961 bacterium Thiobacillus X. A fifth fraction (acidic fraction) contained two additional cytochrome components with x bands at 550 and 557 msi respectively in the reduced state. 2. All the cytochromes appear to be of the c type, are labile to heat and acid and do not combine with carbon monoxide. They are auto-oxidizable to varying degrees. 3. Cytochromes 550 (1) and 557 (1) are basic, and are adsorbed on to Amberlite IRC-50 at pH 7. Their Eo values at pH 7 are +0 20 and +0-15vrespectively. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 6 publications
1
44
0
Order By: Relevance
“…Cell debris was removed by centrifugation (12,000 ϫ g, 15 min), and the supernatant (cell extract [CFE]) was used for the enzyme assay. The activity of thiosulfate oxidase was determined by following the method described by Trudinger (42,43). The reaction mixture (2.5 ml) contained 250 mol of potassium phosphate buffer (pH 7.5), 3 mol of potassium ferricyanide, CFE (300 or 600 g of protein), water, and 20 mol of sodium thiosulfate to start the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Cell debris was removed by centrifugation (12,000 ϫ g, 15 min), and the supernatant (cell extract [CFE]) was used for the enzyme assay. The activity of thiosulfate oxidase was determined by following the method described by Trudinger (42,43). The reaction mixture (2.5 ml) contained 250 mol of potassium phosphate buffer (pH 7.5), 3 mol of potassium ferricyanide, CFE (300 or 600 g of protein), water, and 20 mol of sodium thiosulfate to start the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison with the SDS polyacrylamide gel electrophoresis molecular mass suggests that the cytochrome is present in this fraction in the form of dimeric complexes, although whether these were homogeneous or heterogeneous with the cytochrome c-550 was not determined. Dimerization has not been observed for the two sequenced cytochromes c-556, but has been reported for the cytochrome c-557 from Thiobacillus neapolitanus [19,20] which is likely to be another representative of the same class. Dimerization is also common for the cytochromes c' [21], which are also class I1 cytochromes c [16].…”
Section: Discussionmentioning
confidence: 94%
“…Peck (1960Peck ( , 1962 and others have demonstrated that extracts of thiobacilli in the presence of excess glutathione catalyse the reductive scission of thiosulphate to sulphide and sulphite. The oxidation of thiosulphate to tetrathionate by intact thiobacilli, however, is apparently catalysed by a soluble enzyme located within tp.e bacterial cell (Trudinger 1961b). Moreover the oxidation of thiosulphate to sulphate by T. neapolitanus appears to involve the formation of intermediates containing sulphur from both groups of thiosulphate (Trudinger 1964c), and there is evidence that some of the thiol groups necessary for this oxidation are situated internally (Trudinger 1965).…”
Section: Discussionmentioning
confidence: 99%